ANALISIS INOVASI PELAYANAN PENGAMBILAN PASPOR DRIVE THRU DALAM MENINGKATKAN PELAYANAN PUBLIK DI KANTOR IMIGRASI KELAS I NON TPI BOGOR - Brian Satriyo Adi; Agung Sulistyo Purnomo (Journal of Administration and International Development, 2023)
To carry out its duties as a public service, the Bogor Class I Non-TPI Immigration Office creates the latest service with innovative passport retrieval services through Drive Thru. However, there are obstacles as the Drive-Thru passport collection service goes on, namely vehicle queues due to service mismatches with the implementation of the SOP (Standard Operating Procedure) and the lack of public understanding regarding the implementation of Drive-Thru passport retrieval. The purpose of this study was to determine the implementation of Drive Thru passport retrieval service innovations at the Bogor Non-TPI Class I Immigration Office in improving public services by identifying supporting and inhibiting factors and producing Drive-Thru passports retrieval services. This study uses an approach with formative evaluation, there is data collection through semi-structured interviews with informants, observation, and study documentation to obtain credible data. The results of this study prove that some undoubted strengths and opportunities have not been maximized in the Drive Thru passport retrieval service, using SWOT analysis and SWOT Matrix. Therefore, to look for strengths and opportunities, there is a recommendation that contains efforts to service Drive Thru passports using the SO (Strength-Opportunity) Strategy, namely for a recommendation to be used in the innovation of Drive Thru passport retrieval services to maximize public services by service standards public.